2021
DOI: 10.1002/anie.202109032
|View full text |Cite
|
Sign up to set email alerts
|

Sortase‐Mediated Multi‐Fragment Assemblies by Ligation Site Switching

Abstract: Sortase-mediated ligation (SML) is a powerful tool of protein chemistry allowing the ligation of peptides containing LPxTG sorting motifs and N-terminal glycine nucleophiles. The installation of a sorting motif into the product prohibits the assembly of multiple fragments by SML. Here we report multi-fragment SML based on switchable sortase substrates. Substitution of the Leu residue by disulfide-containing Cys(StBu) results in active sorting motifs, which are inactivatable by reduction. In combination with a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…For example, orthogonal sortases that recognize different peptide motifs as substrates were engineered [ 38 ]. Furthermore, sortase-mediated ligation of multiple protein monomers has been achieved using ‘ligation site switching’ which inactivates the recognition motif in products to eliminate reversible reactions [ 39 ]. These strategies may enable multiple ligations of PBMs, forming high-MW protein oligomers with a defined sequence order.…”
Section: Synthesis Of Repetitive Proteins Using Protein Ligation or P...mentioning
confidence: 99%
“…For example, orthogonal sortases that recognize different peptide motifs as substrates were engineered [ 38 ]. Furthermore, sortase-mediated ligation of multiple protein monomers has been achieved using ‘ligation site switching’ which inactivates the recognition motif in products to eliminate reversible reactions [ 39 ]. These strategies may enable multiple ligations of PBMs, forming high-MW protein oligomers with a defined sequence order.…”
Section: Synthesis Of Repetitive Proteins Using Protein Ligation or P...mentioning
confidence: 99%
“…However, it is necessary to note that these instances do not yet encompass an exhaustive list. In the past few years, remarkable advances of SML have been reported for vaccine engineering, [91] multi-fragment assemblies, [92] proximity-based ligation with shorter reaction times and greater efficiency, [63,67] high-strength force spectroscopy, [93] biomaterials [33b,94] high-throughput screening, [55,95] ligation of d-peptides, [96] and more. In this chapter, several recent examples are highlighted to demonstrate the expanded versatility of SML in combination with other chemical and biological methodologies, such as click chemistry, incorporation of unnatural amino acids (UAAs), and CRISPRbased genome editing (Figure 6).…”
Section: Recent Advancements: Integrating Sortase-mediated Ligation W...mentioning
confidence: 99%
“…In an alternative approach, Bierlmeier et al achieved orthogonal multi-fragment assembly with one enzyme, SaSrtA, via ligation site switching ( Scheme 6A ). 147 The group identified that the leucine in the P4 position of the LPXTG motif could be replaced with l -Cys(StBu) and still be recognised by SaSrtA. Once this residue is reduced to cysteine (and further desulfurized to alanine), the motif is no longer recognised by the enzyme, switching it from an ON state to an OFF state.…”
Section: Orthogonal Activity Of Peptide Ligasesmentioning
confidence: 99%
“…(A) The use of tertbutylthiol cysteine disulfides as leucine isosteres enables the generation of sortase substrates which can then be deactivated by reduction and desulfurisation. 147 (B) Incorporation of azidoacetyl glycyl lysine into proteins enables subsequent reduction using 2-diphenylphosphinobenzoic acid (2DPBA) and labelling using sortases. 148 (C) Extension of this approach to applications with multiple orthogonal sortases enables the synthesis of specific triubiquitin and diubiquitylated SUMO constructs using both internal and Nterminal labelling.…”
Section: Butelase-1mentioning
confidence: 99%